5.7.11 Problems 1001 to 1100

Table 5.583: Solved using series method

#

ODE

Mathematica

Maple

7243

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {2}{9}\right ) y = 0 \]

7244

\[ {}2 x y^{\prime \prime }-\left (2 x +3\right ) y^{\prime }+y = 0 \]

7245

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {4}{9}\right ) y = 0 \]

7246

\[ {}9 x^{2} y^{\prime \prime }+9 x^{2} y^{\prime }+2 y = 0 \]

7247

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (2 x -1\right ) y = 0 \]

7248

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 0 \]

7249

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

7250

\[ {}x y^{\prime \prime }-x y^{\prime }+y = 0 \]

7251

\[ {}y^{\prime \prime }+\frac {3 y^{\prime }}{x}-2 y = 0 \]

7252

\[ {}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }-y = 0 \]

7253

\[ {}x y^{\prime \prime }+y^{\prime }+y = 0 \]

7254

\[ {}x y^{\prime \prime }+\left (x -6\right ) y^{\prime }-3 y = 0 \]

7255

\[ {}x \left (x -1\right ) y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

7256

\[ {}x^{4} y^{\prime \prime }+\lambda y = 0 \]

7257

\[ {}x^{3} y^{\prime \prime }+y = 0 \]

7258

\[ {}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0 \]

7259

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{9}\right ) y = 0 \]

7260

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

7261

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-25\right ) y = 0 \]

7262

\[ {}16 x^{2} y^{\prime \prime }+16 x y^{\prime }+\left (16 x^{2}-1\right ) y = 0 \]

7263

\[ {}x y^{\prime \prime }+y^{\prime }+x y = 0 \]

7264

\[ {}y^{\prime }+x y^{\prime \prime }+\left (x -\frac {4}{x}\right ) y = 0 \]

7265

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (9 x^{2}-4\right ) y = 0 \]

7266

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (36 x^{2}-\frac {1}{4}\right ) y = 0 \]

7267

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (25 x^{2}-\frac {4}{9}\right ) y = 0 \]

7268

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (2 x^{2}-64\right ) y = 0 \]

7269

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 y = 0 \]

7270

\[ {}x y^{\prime \prime }+3 y^{\prime }+x y = 0 \]

7271

\[ {}x y^{\prime \prime }-y^{\prime }+x y = 0 \]

7272

\[ {}x y^{\prime \prime }-5 y^{\prime }+x y = 0 \]

7273

\[ {}x^{2} y^{\prime \prime }+\left (x^{2}-2\right ) y = 0 \]

7274

\[ {}4 x^{2} y^{\prime \prime }+\left (16 x^{2}+1\right ) y = 0 \]

7275

\[ {}x y^{\prime \prime }+3 y^{\prime }+x^{3} y = 0 \]

7276

\[ {}9 x^{2} y^{\prime \prime }+9 x y^{\prime }+\left (x^{6}-36\right ) y = 0 \]

7277

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

7278

\[ {}x y^{\prime \prime }+y^{\prime }-7 x^{3} y = 0 \]

7279

\[ {}y^{\prime \prime }+y = 0 \]

7280

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

7281

\[ {}16 x^{2} y^{\prime \prime }+32 x y^{\prime }+\left (x^{4}-12\right ) y = 0 \]

7282

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (16 x^{4}+3\right ) y = 0 \]

7283

\[ {}2 x y^{\prime \prime }+y^{\prime }+y = 0 \]

7284

\[ {}y^{\prime \prime }-x y^{\prime }-y = 0 \]

7285

\[ {}\left (x -1\right ) y^{\prime \prime }+3 y = 0 \]

7286

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = 0 \]

7287

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

7288

\[ {}\cos \left (x \right ) y^{\prime \prime }+y = 0 \]

7289

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

7290

\[ {}\left (x +2\right ) y^{\prime \prime }+3 y = 0 \]

7291

\[ {}\left (1+x \right ) y^{\prime } = y \]

7292

\[ {}y^{\prime } = -2 x y \]

7293

\[ {}x y^{\prime }-3 y = k \]

7294

\[ {}y^{\prime \prime }+y = 0 \]

7295

\[ {}y^{\prime \prime }-y^{\prime }+x y = 0 \]

7296

\[ {}y^{\prime \prime }-y^{\prime }+x^{2} y = 0 \]

7297

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

7298

\[ {}y^{\prime \prime }+\left (x^{2}+1\right ) y = 0 \]

7299

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

7300

\[ {}y^{\prime }+4 y = 1 \]

7301

\[ {}y^{\prime \prime }+3 x y^{\prime }+2 y = 0 \]

7302

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+30 y = 0 \]

7303

\[ {}\left (x -2\right ) y^{\prime } = x y \]

7304

\[ {}\left (x -2\right )^{2} y^{\prime \prime }+\left (x +2\right ) y^{\prime }-y = 0 \]

7305

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

7306

\[ {}x y^{\prime \prime }+y = 0 \]

7307

\[ {}x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

7308

\[ {}x y^{\prime \prime }+2 x^{3} y^{\prime }+\left (x^{2}-2\right ) y = 0 \]

7309

\[ {}y^{\prime \prime }+\left (x -1\right ) y = 0 \]

7310

\[ {}x y^{\prime \prime }+y^{\prime }+x y = 0 \]

7311

\[ {}2 x \left (x -1\right ) y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

7312

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 x y = 0 \]

7313

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

7314

\[ {}x^{2} y^{\prime \prime }+6 x y^{\prime }+\left (4 x^{2}+6\right ) y = 0 \]

7315

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

7316

\[ {}2 x \left (1-x \right ) y^{\prime \prime }-\left (6 x +1\right ) y^{\prime }-2 y = 0 \]

7317

\[ {}x \left (1-x \right ) y^{\prime \prime }+\left (\frac {1}{2}+2 x \right ) y^{\prime }-2 y = 0 \]

7318

\[ {}4 x y^{\prime \prime }+y^{\prime }+8 y = 0 \]

7319

\[ {}4 \left (t^{2}-3 t +2\right ) y^{\prime \prime }-2 y^{\prime }+y = 0 \]

7320

\[ {}2 \left (t^{2}-5 t +6\right ) y^{\prime \prime }+\left (2 t -3\right ) y^{\prime }-8 y = 0 \]

7321

\[ {}3 t \left (t +1\right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

7322

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {4}{49}\right ) y = 0 \]

7323

\[ {}x y^{\prime \prime }+y^{\prime }+\frac {y}{4} = 0 \]

7324

\[ {}y^{\prime \prime }+\left ({\mathrm e}^{-2 x}-\frac {1}{9}\right ) y = 0 \]

7325

\[ {}x^{2} y^{\prime \prime }+\frac {\left (x +\frac {3}{4}\right ) y}{4} = 0 \]

7326

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (x^{2}-1\right ) y}{4} = 0 \]

7327

\[ {}\left (2 x +1\right )^{2} y^{\prime \prime }+2 \left (2 x +1\right ) y^{\prime }+16 x \left (1+x \right ) y = 0 \]

7328

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-6\right ) y = 0 \]

7329

\[ {}x y^{\prime \prime }+5 y^{\prime }+x y = 0 \]

7330

\[ {}9 x^{2} y^{\prime \prime }+9 x y^{\prime }+\left (36 x^{4}-16\right ) y = 0 \]

7331

\[ {}y^{\prime \prime }+x y = 0 \]

7332

\[ {}4 x y^{\prime \prime }+4 y^{\prime }+y = 0 \]

7333

\[ {}x y^{\prime \prime }+y^{\prime }+36 y = 0 \]

7334

\[ {}y^{\prime \prime }+k^{2} x^{2} y = 0 \]

7335

\[ {}y^{\prime \prime }+k^{2} x^{4} y = 0 \]

7336

\[ {}x y^{\prime \prime }-5 y^{\prime }+x y = 0 \]

7337

\[ {}y^{\prime \prime }+4 y = 0 \]

7338

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

7339

\[ {}\left (x -1\right )^{2} y^{\prime \prime }-\left (x -1\right ) y^{\prime }-35 y = 0 \]

7340

\[ {}16 \left (1+x \right )^{2} y^{\prime \prime }+3 y = 0 \]

7341

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-5\right ) y = 0 \]

7342

\[ {}x^{2} y^{\prime \prime }+2 x^{3} y^{\prime }+\left (x^{2}-2\right ) y = 0 \]